Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 5 - Logarithmic, Exponential, and Other Transcendental Functions - 5.5 Exercises - Page 362: 48


$y’=\frac{2x-3}{x(\ln 3)(x-3)}$

Work Step by Step

$y=\frac{ln(x^2-3x)}{\ln 3}$ $u=ln(x^2-3x)$ $u’=\frac{2x-3}{x^2-3x}$ $v=\ln 3$ $v’= 0$ $y’=\frac{u’v-uv’}{v^2}$ $=\frac{(\frac{2x-3}{x^2-3x})(\ln 3)-(\ln(x^2-3x))(0)}{(\ln 3)^2}$ $y’=\frac{2x-3}{x(\ln 3)(x-3)}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.